Triterpenoids of the roots of Lavandula stoechas ssp stoechas - (:unkn) unknown (GOVI-VERLAG GMBH, 2001)
The roots of Lavandula stoechas ssp. stoechas afforded eleven known triterpenes, two steroids and two aromatics, in addition to two new triterpenes, 18-hydroxy-27-norolean-12,14-dien-30-al-28-oic acid and 3 beta -Iiydroxy-1-oxo-olean-12-ene-30-al-28-oic acid. Their structures were determined by spectroscopic analyses. The chloroform extract and some isolated compounds were evaluated for their growth inhibitory activity against several mammalian cell lines.